Incidence of perianaesthetic complications experienced during feline bronchoscopy: a retrospective study. Issue 10 (October 2019) - Tucker, Philippa K; MacFarlane, Paul
Objectives: The aim of this study was to report the incidence of anaesthetic complications associated with feline bronchoscopy. Methods: This was a retrospective analysis of anaesthetic records and electronic case logs of feline bronchoscopies at two university hospitals (centres B and L) between January 2013 and December 2015. A two-tailed Fisher's exact test was used for comparison of variables and outcomes between centres. Results: Seventy-nine cases were included. Desaturation (SpO2 <90%) was the most frequently encountered complication, reported in 24 cats (30.3%); centre B reported significantly less desaturation than centre L (22.4% vs 52.4%; P = 0.014). The use of an endotracheal tube or laryngeal mask airway resulted in a lower incidence of desaturation (22.9% vs 22.2%) than the use of a tracheal catheter through which oxygen was insufflated (48.0%). The latter method was associated with an increased incidence of desaturation ( P = 0.034). Patients to which terbutaline was administered had a lower incidence of desaturation (27.5%) than those that did not receive it (35.7%), although this was not statistically significant ( P = 0.46). Airway management method and the use of terbutaline differed significantly between centres, as did the profile of complications. Pneumothorax was encountered in two cats (2.5%) and cardiac arrest resulting in the death in one of these cats (1.3%). Conclusions and relevance: Desaturation is a frequently encountered complication during and after bronchoscopy. Airway management method and the use and timing of terbutaline warrant prospective evaluation for their role in decreasing the incidence of desaturation. Bronchoscopy is a high-risk procedure with frequent requirement for post-procedure oxygen supplementation. Pneumothorax and cardiac arrest are potential complications.